Harmine-mediated Reduction of Bone Cancer Pain in Rats Correlates With Suppressed DYRK1A/NF-κB Signaling Axis - Shuyao Zhang; Shang Zheng; Jia Jin; Yuhua Li; Liping Chen; Junjie Lin; Ming Yao; Longsheng Xu (Journal of Integrative Neuroscience)
Background: Bone cancer pain (BCP) is a prevalent chronic pain condition and a common clinical symptom in patients with advanced cancer. It significantly affects the mobility and quality of life of patients; however, current treatments offer limited efficacy. Harmine, a beta-carboline alkaloid extracted from Peganum harmala, exhibits anti-inflammatory, anxiolytic, analgesic, and neuroprotective properties. However, its antinociceptive properties and mechanisms in BCP models remain unclear. This study aimed to systematically investigate the analgesic effects of Harmine in rats with BCP and explore its underlying molecular mechanisms. Methods: Using databases such as SwissTargetPrediction and Polypharmacology Browser, molecular docking analysis, behavioral tests, and biochemical analysis, we comprehensively evaluated the effects of Harmine in the BCP model. Results: The results demonstrated that Harmine significantly alleviated BCP induced by Luciferin-Malignant Atypical Discrete Breast 106 cells (LUC-MADB106) in a dose-dependent manner. Intrathecal administration of Harmine significantly inhibited the upregulation of dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) expression and the activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway in the spinal cord dorsal horn (SCDH) of rats with bone cancer. Conclusions: These findings suggest that Harmine has significant therapeutic potential for alleviating BCP hyperalgesia, providing a foundation for the future development of new drugs targeting BCP.